Advanced Mathematical Thinking dalam Pembelajaran Matematika Tingkat Lanjut - Andri Suryana; Seruni Seruni (JKPM (Jurnal Kajian Pendidikan Matematika), 2019)
Students' Advanced Mathematical Thinking in advanced mathematics courses were still relatively low. This happens because the lecturer did not provide opportunities for students to be able to construct their own mathematical concepts and students were still weak in mastering concepts in prerequisite courses. The lecturer is expected to provide opportunities for students to be active in learning and be able to construct their own advanced mathematical concepts through the implementation of innovative learning based on constructivism to improve students' Advanced Mathematical Thinking in advanced mathematics courses. The purpose of this literature study is to find out more about advanced mathematical thinking and its components (representation, abstraction, creative thinking, and proof) in advanced mathematics learning and how to develop it.